Perlindungan Hukum Terhadap Tindakan Debt Collector dalam Penarikan Objek Jaminan Fidusia Oleh Perusahaan Pembiayaan Kendaraan - Erlika Sari; Puspitasari Rusdi; Hairul Saleh Satrul (Cattleya Darmaya Fortuna, 2026)
Consumer protection stipulates that every consumer has the right to obtain legal protection and fair dispute resolution mechanisms, as provided in Article 4 letter (e) of Law Number 8 of 1999 on Consumer Protection. In Indonesia, there has been a significant increase in public interest in purchasing vehicles through credit schemes offered by financing companies, which has given rise to various legal issues. In many cases, debtors experience default (wanprestasi). This condition has led most financing companies (leasing companies) to employ third parties, commonly referred to as debt collectors, to conduct debt collection activities against consumers (debtors). However, in practice, numerous incidents have occurred in which consumers’ fiduciary objects are forcibly repossessed due to delayed installment payments. This study examines the legal protection afforded to consumers in the repossession of fiduciary collateral objects, as well as the constraints and recommendations necessary to ensure compliance with the applicable laws and regulations. This research employs a normative juridical approach, conducted by examining statutory regulations related to the actions of debt collectors in the repossession of fiduciary objects. The results of the study indicate that the execution of fiduciary collateral objects may only be carried out if there is a voluntary agreement between the creditor and the debtor, or through a court decision. Therefore, actions undertaken by third parties or debt collectors that involve the forcible repossession of vehicles without a clear and lawful legal basis constitute a violation of the law.